Performance analysis of different designs of all-optical D flip flop - Archana, K; Manohari, R; prince, Shanthi (International Journal of Engineering and Technology, 2018)
All optical flip flops play an important role in optical networks as well as in the field of optical computing. Optical memories are used for storing decisions in photonic packet routers temporarily. In this paper all optical D-flip flop is designed based on all optical gates. The nonlinear effects such as XGM (Cross Gain Modulation), XPM (Cross Phase Modulation) and FWM (Four Wave Mixing) are used to design all optical gates. We designed the D flip flop based on two logic that are NAND-NAND logic and NAND-NOR logic. The performance of both the designs is analyzed and the functionality of all optical D-flip-flop is verified using the truth table. It is proved that NAND-NAND logic is more effective than NAND-NOR logic.